Finite element simulation and structure optimization of HTS solenoid - Cong, Menglong; Zhang, Shanshan; Chen, Xueyan; Zhou, Kunpeng (Frontiers in Materials, 2022)
When the current passing through a high temperature superconducting (HTS) coil that exceeds a critical value, the properties of the materials which make up the coil will fail, generating large amounts of heat and even causing serious accidents. Aiming at the above safety problem, this paper took three solenoid magnets with different structures as the object, and conducted a simulation study on their electromagnetic performance through finite element method (FEM). The magnetic field intensity H was taken as the dependent variable of the control equations of the physical field. With the aid of the partial differential equation (PDE) interface of the simulation software used, the control equations were easily constructed. The pancake coil wound by many turns of ribbon conductors was abstracted as a bulk-like conductor with the same cross-sectional area. The main idea of this equivalent replacement is to simplify the internal structure of the device without affecting its electromagnetic behavior, which can accelerate the convergence speed of the simulation process and reduce the CPU burden. Models of solenoid magnets with rectangular, trapezoidal and inverted trapezoidal cross sections were established by stacking many pancake coils. The simulation results corresponding to these models show that the solenoid magnet with trapezoidal cross-section has the largest critical current and most uniform density distribution. Such advantages not only reduce the risk of superconducting material failure due to overheating at both ends, but also fully exploit the current carrying capacity of the coil in the middle area of the solenoid.